Corporate Governance and Legal Issues in Management: Global Perspectives - Kamila Mariam Iftikhar ,; Huma Salman,; Yannick Stéphane Désiré ATTHOS,; Qazi Shehryar,; Tariq Rafique, (Dialogue Social Science Review (DSSR), 2025)
Corporate governance and legal factors are central to organizational performance in the global business world. Knowledge of how board composition, regulation, and ethical leadership relations affect performance through organizational transparency is crucial for MNCs to operate in different legal and cultural environments. The purpose of this study is to analyze the following variables; Board composition, Regulatory compliance, and Ethical leadership as independent variables organizational performance as the dependent variable, and Organisational transparency as mediator. A quantitative research therefore used a structured questionnaire that was e-mailed to senior executives, board members, and managers in multinational corporations. The survey consisted of Likert scale questions that reflected the major research variables. The research gathered 100 questionnaires. In quantitative data, Descriptive analysis, Normality test Shapiro-Wilk test, Reliability test-Cronbach alpha, and construct validity Factor analysis. Shapiro-Wilk analysis revealed that none of the variables in the study had a normal distribution since the p < 0.05 global business environment. Understanding how board composition, regulatory adherence, and ethical leadership influence performance, mediated by organizational transparency, is essential for multinational corporations navigating diverse legal and cultural landscapes. This study aims to examine the relationships between board composition, regulatory compliance, and ethical leadership (independent variables) on organizational performance (dependent variable), with organizational transparency acting as a mediating variable. A quantitative research design was employed, utilizing a structured questionnaire distributed electronically to senior executives, board members, and managers of multinational corporations. The survey comprised Likert-scale questions assessing the key variables. A total of 100 responses were collected. Data analysis included descriptive statistics, the Shapiro-Wilk test for normality, Cronbach's Alpha for reliability, and factor analysis for construct validity. The Shapiro-Wilk test indicated that the data did not follow a normal distribution (p < 0.05 for all variables). Many survey items within the reliability analysis had low internal consistency and evidenced a negatively valued Cronbach’s Alpha of -0.097. The factor analysis showed that constituents of the first five factors’ explained an insignificant element of the total variance (highest constituent = 3.24%) and which posed construct validities. Based on these results, it may be inferred that there is a compromise in the validity of the survey instrument to capture the intended constructs. The study identifies major methodological limitations for evaluating corporate governance and legal measures worldwide. The status refers to elements of poor reliability and low explained variance, a lack of normality, all of which signal that the research instrument needs further fine-tuning. However, this research indicates the need to adopt governance practices and legal compliance that will further increase organizational performance. In future research, efforts should be made to improve measurement validity and reliability and more attention must be paid to distribution problems by attempting non-parametric analytical tools.